‘Handle With Care’? Person-Centred Live-in Care Provided by Posted Workers and Other Care-Related Phenomena in the EU - Kiełbasa, Marcin (Medicine, Law & Society, 2025)
This article examines the growing phenomenon of live-in care in the European Union, with particular focus on services provided by posted workers, including third-country nationals. It situates live-in care within the broader EU socio-legal framework, tracing the evolution of recent policy developments such as the European Pillar of Social Rights, the European Care Strategy, and documents arising therefrom. The article analyses the latest phenomena in cross-border live-in care, including deinstitutionalisation of care, highlighting how person-centred and community-based models are reshaping the field. Special attention is devoted to gender dimensions, including the disproportionate burden on women and the ’daughterhood penalty’ and ’motherhood penalty’. By linking legal, economic, and social aspects, the article assesses whether EU policies effectively address current challenges in that regard and their future impact concerning more sustainable care provision.